An Investigation on Electric Dipole Transitions of Pt LXVII - Gülay Günday Konan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2022)
In the present work, we have reported the energy levels, wavelengths, weighted oscillator strengths, and transition probabilities for electric dipole (E1) transitions of magnesium like platinum (Pt LXVII, Z=78). Accurate knowledge of Mg-like ions are of great importance for astrophysics, plasma, and thermonuclear fusion research. The atomic data are calculated with the AUTOSTRUCTURE code, where relativistic corrections are introduced according to the Breit–Pauli distorted wave approach. In the calculations, quantum electrodynamics effects and correlation contributions have been considered. The present results are in good agreement with other available values. There are no experimental works for Pt LXVII in the literature. We predict new theoretical data for several levels will be helpful for future experimental works.